Yeast metabolic state identification by fiber optics spectroscopy - Castro, C. C. (2009)
In this manuscript we explore the feasibility of using LWUV-VIS-SWNIR (340 - 1100 nm) spectroscopy to classify Saccharomyces cerevisiae colony structures in YP agar and YPD agar, under different growth conditions, such as: i) no alcohol; ii) 1 % (v/v) Ethanol; iii) 1 % (v/v) 1-Propanol; iv) 1 % (v/v) 1- butanol; v) 1 % (v/v) Isopropanol; vi) 1 % (v/v) (±)-1-Phenylethanol; vii) 1 % (v/v) Isoamyl alcohol; viii) 1 % (v/v) tert-Amyl alcohol (2-Methyl-2-butanol); and ix) 1 % (v/v) Amyl alcohol. Results show that LWUV-VISSWNIR spectroscopy has the potential for yeasts metabolic state identification once the spectral signatures of colonies differs from each others, being possible to acheive 100% of classification in UV-VIS and VISSWNIR. The UV-VIS region present high discriminant information (350-450 nm), and different responses to UV excitation were obtained. Therefore, high precision is obtained because UV-VIS and VIS-NIR exhibit different kinds of information. In the future, high precisio n analytical chemistry techniques such as mass spectroscopy and molecular biology transcriptomic studies should be performed in order to understand the detailed cell metabolism and genomic phenomena that characterize the yeast colony state.